EFFECT OF PLANTING DATE ON SEED SIZE TUBER YIELD OF POTATO IN NILGIRIS - Muthuraj, R.; Ravichandran, G.; Krishna Prasad, K S.; Singh, Sarjeet (Potato Journal, 2013)
A field experiment was conducted during summer seasons of 2003 and 2004 at CPRS, Muthorai with three dates of planting i.e. April 21st, May 22nd and June 21st using randomised block design with four replications using three cvs., viz., Kufri Giriraj, Kufri Jyoti and Kufri Swarna. April 21st planting produced more number of seed size tubers and yield in cvs. Kufri Giriraj and Kufri Jyoti, whereas June 21st planting performed well with cv. Kufri Swarna by producing higher number of seed size tubers and yield. In cv. Kufri Jyoti among the three dates of planting, April 21st planting produced highest yield of seed size tubers (51.25q ha-1) followed by June 21st planting (50.23q/ha-1). In case of cv. Kufri Giriraj, maximum seed size tuber yield (46.5 q/ha) was obtained in April 21st planting followed by 21st June planting (32.71q/ha). Whereas, cv. Kufri Swarna produced higher seed size tuber yield (21.68q ha1) in 21st June planting. Number of Seed size tubers also followed the similar trend as that of yield. The interaction effect between date of planting and varieties were significant with respect to grade wise tuber yield. The results showed that the crop in Nilgiris should be planted around 21st April for achieving the highest yield and number of seed size tubers in cvs. Kufri Jyoti and Kufri Giriraj while Kufri Swarna may be planted on 21st June.